Metabolic syndrome in polycystic ovary syndrome. - Barber, T; McCarthy, M; Franks, S; Wass, J (2007)
Both metabolic syndrome (MS) and polycystic ovary syndrome (PCOS) are common among women. The exact prevalence of MS in women with PCOS is dependent upon the diagnostic criteria used for each. However, the frequent co-occurrence of both MS and PCOS in women is suggestive of a common aetiology. In this short review article we argue that insulin resistance, as a consequence of abdominal obesity, may represent such a common aetiology. We also review the literature on the prevalence of MS in women with PCOS and consider the impact that the particular criteria used to diagnose both MS and PCOS may have had on these estimates of prevalence.